The cosmic journey of dust grains – from nucleation to planetary system - Lund, Kira; Johansen, Anders; Agertz, Oscar (Monthly Notices of the Royal Astronomical Society, 2025)
Dust is essential to the evolution of galaxies and drives the formation of planetary systems. The challenge of inferring the origin of different pre-solar dust grains from meteoritic samples motivates forward modelling to understand the contributions of low- and high-mass stars to dust in our Solar system. In this work we follow the evolution of dust with tracer particles within a hydrodynamical simulation of a Milky Way-like isolated disc galaxy. We find that nearly half of the grains released from stars lose less than 10 per cent of their initial mass due to thermal sputtering in the interstellar medium (ISM), with an average degree of atomization ∼10 per cent higher for dust grains released by supernovae (SNe) relative to asymptotic giant branch (AGB) star grains. We show through SN remnant model variations that SN dust survival is primarily shaped by the SN bubble environment in the first million years (Myr) after the explosion rather than by its evolution during 102—103 Myr in the ISM. The AGB/SN ratio of dust grains incorporated into newly formed stars approaches 0.8 after a few hundred Myr of galactic evolution. Our analysis also shows that star-forming particles with short (<10 Myr) free-floating time-scales in the ISM are predominantly released from SNe rather than AGB stars.
Keywords: galaxies: evolution; galaxies: star formation; methods: numerical; planetary systems